Pengembangan Lembar Kerja Mahasiswa (LKM) Berbasis Inkuiri Kontekstual Materi Mikrobiologi Air pada Mahasiswa Pendidikan Biologi UNIMED - Yusnita Anwar Nasution; Hasruddin Hasruddin; Tumiur Gultom (Universitas Sebelas Maret, 2017)
The study aims to determine: (1) The results expert material validation of worksheet that has been developed;(2) The results of design experts validation of worksheet that has been developed; (3) Response of lecturer ofmicrobiology subject to worksheet that has been developed; (4) Perception of University of Medan BiologyEducation students to Worksheet that has been developed; (5) The eligibility of Worksheet for BiologyEducation students of State University of Medan. This development study uses a modified Borg & Gall modelas needed to produce a product of a contextual inquiry-based worksheet. The subjects test consisted of a teamof material experts, a team of design specialists, 3 (three) students individual testing of biological education, 9(nine) students of Biology education small group trial, 20 (twenty) students of Biology education limited fieldtrial. Data collected using questionnaires. The results of material expert validation to microfinance basedworksheet in context of water microbiology materials that have been developed with the feasibility of thecontents show the percentage of 93.75% included in the category of very good; Feasibility of presentationshows the percentage of 91.44% included in the category of very good; The feasibility of the contextual inquirycomponent indicates the percentage of 87.82% in the category of good good; The design validation results showthat 89.06% percentage is included in the category of very good; The result of the assessment by the lecturershows the percentage of 93.75% is included in the category of very good; Individual tests show the percentageof 86,66% included in the category of very good; Small group test showed 87.22% percentage included in thecategory of very good; The test of the restricted group shows the percentage of 91.12% included in the thecategory of very good. Test based on the data the product worksheet based on inquiry of contextual materialof water microbiology which have been developed feasible to be used for student as worksheet in Microbiologycourse.